2016
DOI: 10.1016/j.joca.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine modulates osteoarthritic chondrocyte metabolism and inflammatory responses

Abstract: NE affects chondrocytes from OA cartilage regarding inflammatory response and its cell metabolism in a dose dependent manner. The sympathetic nervous system (SNS) may have a dual function in OA pathology with preserving a stable chondrocyte phenotype via β-AR signaling and OA pathogenesis accelerating effects via α-AR signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 39 publications
4
55
2
1
Order By: Relevance
“…Various degrees of local inflammation might therefore evoke changes in innervation pattern of OA synovium comparable to RA and might also induce TH expression in joint cells, providing a local source for NE as has been shown for synovial macrophages [49]. In this line, our group demonstrated that chondrocytes of OA cartilage express TH in all three cartilage zones with the weakest staining intensity in the deep zone [54]. With that, the cells possess the prerequisite to induce an anti-inflammatory response in their immediate environment, perhaps serving as a primarily protective measure in OA.…”
Section: Sensory and Sympathetic Nerve Fibers In Osteoarthritic Jomentioning
confidence: 82%
See 3 more Smart Citations
“…Various degrees of local inflammation might therefore evoke changes in innervation pattern of OA synovium comparable to RA and might also induce TH expression in joint cells, providing a local source for NE as has been shown for synovial macrophages [49]. In this line, our group demonstrated that chondrocytes of OA cartilage express TH in all three cartilage zones with the weakest staining intensity in the deep zone [54]. With that, the cells possess the prerequisite to induce an anti-inflammatory response in their immediate environment, perhaps serving as a primarily protective measure in OA.…”
Section: Sensory and Sympathetic Nerve Fibers In Osteoarthritic Jomentioning
confidence: 82%
“…An earlier study performed by Lai et al confirmed only the expression of β2-AR on growth plate chondrocytes from ribs of embryonic E18.5 mice [72]. Studies on cartilage tissue explants isolated from OA patients after endoprothetic surgery and on chondrogenic progenitor cells obtained from human OA cartilage explants revealed that also under degenerative conditions, β2-AR and α2-AR are present [54,70]. As it is suggested that many biomechanical pathways in OA pathogenesis are altered, it is conceivable that β2-AR might contribute to disease development related to overloading of cartilage, because β2-adrenergic drugs have been shown to influence mechanical events in bone tissue [21,73].…”
Section: Sensory and Sympathetic Neurotransmitters And Their Recepmentioning
confidence: 99%
See 2 more Smart Citations
“…These pathways consist of adrenaline signaling, alpha-linolenic acid and retinol metabolism, vitamin A deficiency, and amino acid degradation. Adrenaline signaling through norepinephrine (m/z: 170.0807, adduct: M+H + ) previously has been linked to increased apoptosis and the reduction of chondrocyte proliferation in OA cell cultures (Lorenz et al, 2016). Anti-inflammatory and tissue protective effects have been shown in 1:1 to 6:1 ratios of linoleic acid (LA) to alpha-linolenic acid (ALA) inhibiting the decomposition of connective tissue such as type II collagen compared to higher ratios ( e.g.…”
Section: Discussionmentioning
confidence: 99%